The Stabilising Role of US Federal Fiscal Institutions – What Lessons for the Euro Area? - Cinzia Alcidi; Gilles Thirion (Intereconomics, 2017)
The classic argument for a euro area “fiscal capacity”, understood in this contribution as a centralised fiscal stabiliser, revolves around the need to dampen the effects of asymmetric shocks. According to those preaching this conventional wisdom, a common fiscal stabiliser designed along the lines of the US federal fiscal system would have stabilised incomes in member states hit the hardest, thereby avoiding the divergence that has unfolded in the aftermath of the financial crisis between the South, led by Italy and Greece, and the North, led by Germany and the Benelux countries.
Keywords: 330